2017
DOI: 10.1016/j.eats.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Cutting Instrument for Fresh Osteochondral Distal Tibia Allograft Preparation: Treatment of Glenoid Bone Loss

Abstract: Glenoid bone loss presents a major risk for glenohumeral instability that has been well recognized as a cause of instability recurrence after attempted Bankart repair, and although most surgeons consider the Latarjet procedure as the gold standard, failures can occur with this technique as well and the search for alternative grafts to address glenoid bone loss is a major topic of ongoing research in the field. Of these techniques, the distal tibia allograft (DTA) has been shown to provide an excellent option t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 10 DTA is the preferred choice in FBB procedure with many advantages, including no donor site morbidity, restoration of a large glenoid defect, excellent articular congruency with the humeral head, restoration of biomechanics of the glenoid, and a robust option for treatment following a failed Latarjet procedure. 5 , 11 Moreover, fresh DTA glenoid reconstruction for recurrent shoulder instability has shown an improvement in functional outcome at an average follow-up of 45 months, with a high allograft healing rate of 89%, minimal graft resorption (3%), and no case of recurrent instability. 8 A recent matched cohort analysis showed that DTA had excellent outcomes after surgery with low recurrent instability rates, similar to the well-accepted Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 DTA is the preferred choice in FBB procedure with many advantages, including no donor site morbidity, restoration of a large glenoid defect, excellent articular congruency with the humeral head, restoration of biomechanics of the glenoid, and a robust option for treatment following a failed Latarjet procedure. 5 , 11 Moreover, fresh DTA glenoid reconstruction for recurrent shoulder instability has shown an improvement in functional outcome at an average follow-up of 45 months, with a high allograft healing rate of 89%, minimal graft resorption (3%), and no case of recurrent instability. 8 A recent matched cohort analysis showed that DTA had excellent outcomes after surgery with low recurrent instability rates, similar to the well-accepted Latarjet procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect cuts may compromise the congruency for restoring the native joint mechanics and increase risk of intraoperative complications, such as graft fracture or articular cartilage injury. 11 Our technique for DTA preparation has several advantages. First, to accommodate the specific glenoid version, the allograft is angle cut by the cutting block (“CUT#2”) that is determined preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Whole, fresh distal tibias were obtained from a tissue bank, and 28 DTA grafts were harvested in a standardized fashion using a graft harvest station to ensure reproducibility. 3 The grafts were donated by an orthopaedic allograft supply company (JRF Ortho). Unfortunately, the age and sex of the donors were not available, although previous studies have shown that the suitability of grafts is independent of these factors.…”
Section: Methodsmentioning
confidence: 99%